Complex regulation of Cav2.2 N-type Ca2+ channels by Ca2+ and G-proteins. - Jessica R Thomas; Jinglang Sun; Juan De la Rosa Vazquez; Amy Lee (PLoS ONE)
G-protein coupled receptors inhibit Cav2.2 N-type Ca2+ channels by a fast, voltage-dependent pathway mediated by Gαi/Gβγ and a slow, voltage-independent pathway mediated by Gαq-dependent reductions in phosphatidylinositol 4,5-bisphosphate (PIP2) or increases in arachidonic acid. Studies of these forms of regulation generally employ Ba2+ as the permeant ion, despite that Ca2+ -dependent pathways may impinge upon G-protein modulation. To address this possibility, we compared tonic G-protein inhibition of currents carried by Ba2+ (IBa) and Ca2+ (ICa) in HEK293T cells transfected with Cav2.2. Both IBa and ICa exhibited voltage-dependent facilitation (VDF), consistent with Gβγ unbinding from the channel. Compared to that for IBa, VDF of ICa was less sensitive to an inhibitor of Gα proteins (GDP-β-S) and an inhibitor of Gβγ (C-terminal construct of G-protein coupled receptor kinase 2). While insensitive to high intracellular Ca2+ buffering, VDF of ICa that remained in GDP-β-S was blunted by reductions in PIP2. We propose that when G-proteins are inhibited, Ca2+ influx through Cav2.2 promotes a form of VDF that involves PIP2. Our results highlight the complexity whereby Cav2.2 channels integrate G-protein signaling pathways, which may enrich the information encoding potential of chemical synapses in the nervous system.